К вопросу о минимизации деформаций при термической обработке износостойкого плакированного проката - Загорянский, В. Г.; Шаповал, А. А.; Мосьпан, Д. В. (НТУ "ХПИ", 2014)
В статье уточнен известный расчетный метод (И. А. Рябцев с сотрудниками, ИЭС им. Е. О. Патона) определения деформации плакированного износостойкого проката при закалке. Рассмотрен случай композиции Ст3+У20Х6Т2Д (карбидная износостойкая сталь), применяемой в условиях абразивного изнашивания в сельскохозяйственном машиностроении. Уточнены результаты расчета прогиба биметаллических пластин. В модель расчета прогиба пластин, кроме температуры закалки, введены дополнительные влияющие параметры. На основе этого метода разработана оптимизационная модель расчета и проведена ее программная реализация в программе Microsoft Excel

In the paper known calculation method (I. A. Ryabtsev with colleagues, The E. O. Paton Electric Welding Institute) of determination of deformation of clad wear-resisting rolled metal at hardening is specified. A case of composition Ст3+У20Х6Т2Д (carbid wear-resistance steel) used for agricultural machinery industry in the conditions of abrasion damage is considered. Results of calculation of bending flexure of bimetal plates is specified. The additional influencing parameters to the model of calculation of bending flexure of plates besides of temperature of hardening is entered. On a basis of this method an optimization model of calculation is developed and its program realization in program Microsoft Excel (add-in Solver) is fulfilled
To the problem of minimizing the deformation during heat treatment of wear-resistant clad rolling
Keywords: двухслойный лист; радиус кривизны; температура закалки; оптимизация; износостойкая сталь; абразивное изнашивание; wear-resisting rolled metal; two-layered sheet; minimization of deformations; heat treatment; radius of curvature; temperature of hardening; optimization